The Long Birth of a “Furious Revisionist.” Journalistic Activity of Roman Zimand in the Years 1955–56 - Olaszek, Jan (Sensus Historiae, 2021)
The article is part of the discussion on Stalinism in Poland, the thaw process and the attitudes of the Polish intelligentsia towards communism. The text contains an analysis of Roman Zimand’s journalism in the years 1955–56. The author analyzes the following problems: the role of politically engaged culture and art, the attitude to the process of settlement with socialist realism and Stalinism, the vision of the roles played by the communist party, the attitude to the most important events in politics and culture.